Lamb behaviour during and shortly after tail-docking - M Teubes; AJ Scholtz; K Dzama; SWP Cloete (South African Journal of Animal Science, 2025)
Routine husbandry procedures for lambs are increasingly scrutinised for their animal welfare implications. One such procedure is tail-docking, which is commonly performed to prevent breech blowfly strike. Although tail-docking is considered painful for lambs, the precise level of pain remains unquantified. While proponents argue that the long-term benefits outweigh the temporary pain caused; further investigations into the welfare implications of tail-docking are needed. This study assessed Merino lambs at an average docking age of 14 ± 3 days across five cohorts, each comprising 25–35 ewes and their lambs (n = 228). Two treatments were administered: the Control group lambs were left intact and undocked, while the Treatment group lambs were tail-docked. Lambs were randomly assigned to either group, with birth type and sex as stratifying factors. Observational data were collected during three periods: 1. during the tail-docking/sham procedure following the established protocol; 2. during a two-minute period immediately post-docking, upon returning to their dams; and 3. during a two-minute period 10 minutes post-docking. Signs of discomfort were evident during tail-docking and persisted at two and 10 minutes post-procedure. During the docking/sham procedure, undocked lambs were more likely to remain calm, whereas docked lambs exhibited signs of distress, including restlessness, kicking, bleating, and tense facial expressions. Observations at two minutes post-docking aligned with those recorded at 10 minutes post-docking, indicating sustained discomfort. These findings suggest that tail-docking results in both immediate and longer-term discomfort. Further research should assess whether the long-term benefits of tail-docking justify the associated pain.